Developing Islamic Finance in the Philippines - Mylenko, Nataliya (World Bank, Washington, DC, 2016)
This report was prepared as part of the World Bank engagement in the Philippines to support Islamic Finance and Financial Inclusion. It provides an overview on the context for the development of Islamic finance in the Philippines and is accompanied by two focused reports providing further detail and suggestions on enhancing financial inclusion in the Philippines through Islamic microfinance and assessment of the status of financial inclusion in Autonomous Region in Muslim Mindanao (ARMM)and the proposed Bangsamoro territory. The term Islamic finance is used to refer to financial activities conforming to Islamic Law (Shari‘ah). One of the main principles of the Islamic finance system is the prohibition of the payment and the receipt of ribā (interest) in a financial transaction. A pure debt security is replaced with an “asset-based” security, direct financing of a real asset, and different forms of partnerships of which equity financing is the most desirable.The following key principles guide Islamic Finance: i) Prohibition of interest on transactions (ribā); ii) Financing must be linked to assets (materiality); iii) Engagement in immoral or ethically problematic businesses not allowed (e.g., gambling or alcohol production); iv) Returns must be linked to risks. Table 1 provides a summary description of basic financial instruments.Over the past decade Islamic finance has emerged as an effective tool for financing development worldwide, including in non-Muslim majority countries. Discussion and interest in Islamic finance has also appeared on G20 discussions. Major financial markets are discovering solid evidence that Islamic finance has already been mainstreamed within the global financial system – and that it has the potential to help address the challenges of ending extreme poverty and boosting shared prosperity.In summary, Islamic finance is equity-based, asset-backed, ethical, sustainable, environmentally- and socially-responsible finance. It promotes risk sharing, connects the financial sector with the real economy, and emphasizes financial inclusion and social welfare.